Seed quality of early maturing soybean cultivars from different sowing dates - Pereira, Elainy Botelho Carvalho; Pereira, Ailton Vitor; Fraga, Antônio Carlos (Pesquisa Agropecuaria Brasileira, 2000)
This work aimed to evaluate the physiological and sanitary seed qualities of seven early maturing soybean cultivars (EMGOPA 304, EMGOPA 309, EMGOPA 316, EMBRAPA 1, EMBRAPA 4, Rainha and Itiquira), obtained from three sowing dates (conventional, on Nov. 20; early, on Oct. 30; and delayed, on Dec. 30/1995), at Goiânia, GO, Brazil. The experiment was carried out in split plot and randomized complete block design, with three replications. Physiological quality was evaluated by germination test in rolled paper and in sand seed bed and by seed vigor through the tetrazolium test. Sanitary quality was evaluated by means of the Blotter test. The results showed that physiological and sanitary seed qualities are influenced by the cultivars and the sowing dates. Early sowing in October results in seed quality losses caused by the adverse environment moisture conditions and the threshing mechanical damages, allied to the occurrence of seed pathogen infection, specially Phomopsis sojae. High threshing mechanical damages are the cause of seed quality losses in the delayed sowing at the end of December.